Monoclonal antibodies to a particulate superoxide-forming system stimulate a respiratory burst in intact guinea pig neutrophils. - Berton, G (1986)
Monoclonal rat antibodies were produced against a subcellular preparation of phorbol 12-myristate 13-acetate (PMA)-stimulated guinea pig neutrophils that retains NADPH-oxidase activity. Two antibodies, 1A10.4 and IG4, were isolated that bind to a surface antigen restricted to guinea pig neutrophils from bone marrow and peritoneal exudate and to macrophages and that trigger a respiratory burst in neutrophils in the presence of cytochalasin B. Intact antibody 1A10.4, subclass IgG2c, can trigger superoxide anion release directly; F(ab')2 fragments of 1A10.4 and intact IG4 require further cross-linking by F(ab')2 fragments of anti-rat immunoglobulin antibody. Both antibodies recognize the same antigen, a proteolipid of apparent molecular mass 10 kDa. Immunoprecipitation of solubilized oxidase activity with 1A10.4 brings down this activity as part of a macromolecular complex. Surface expression of the antigen is increased on treatment of cells with both PMA and cytochalasin B. 1A10.4 also triggers release of the granule enzyme beta-glucuronidase. Triggering of a respiratory burst by the antibodies appears distinct from the PMA and fMet-Leu-Phe signalling systems. These studies indicate that the antigen defined by antibodies 1A10.4 and IG4 becomes associated with the superoxide anion-generating system of neutrophils but may play a more general role in signal transduction in phagocytic cells.